THE ROLE OF STAKEHOLDERS AND EXOGENOUS VARIABLES AFFECTING THE OUTCOME OF SOCIAL FORESTRY POLICIES IN CENTRAL SULAWESI, INDONESIA - Akhbar; Golar; Naharuddin; Massiri, Sudirman Daeng; Malik, Adam; Pribadi, Hendra; Rahman, Abdul; Maiwa, Arman (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Social forestry (SF) is Indonesian policy that aims to provide legal access to the community in utilizing forest resources and seek sustainable forest management, contributing to the community's economic improvement. This study examines the action situation of implementing SF policies in Central Sulawesi Province and analyses the roles of stakeholders and exogenous variables determining SF policies' outcomes. The Institutional Analysis Development (IAD) framework was applied in the study by identifying and analyzing the action situation and its relation to the implementation of SF in Central Sulawesi. The research revealed that the implementation of social forestry in Central Sulawesi Province is not optimal. This is indicated by the fact that local institutions have not achieved self-governance, the sustainability of forest function has not been realized, and the social forestry programs have not significantly increased the income of the local community.. Implementing the SF policy depends on the facilitator's capacity at the site level and stakeholders' support. The action for strengthening social forestry at site levels requires strong collaboration among stakeholders by considering their interests and capacities. These findings suggested the urgency of future research to examine strategies for governing the role of stakeholders in boosting local institutional capacity and the outcomes of SF policies.